Production index and quality of eggs of laying hens subjected to different methods of beak trimming - Vieira Filho, Javer Alves [UNESP]; Garcia, Edivaldo Antonio [UNESP]; Oba, Eunice [UNESP]; Santos, Tiago Antonio dos [UNESP]; Silva, Anderson Pontes; Molino, Andrea Britto; Lima Almeida Paz, Ibiara Correia de [UNESP]; Araujo Baldo, Grace Alessandra de [UNESP] (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to evaluate the effect of beak trimming, by hot blade or infrared radiation, on the production indicators and egg quality of three laying hen strains in the first week of life, and whether a second beak trimming would be necessary in the tenth week. Birds were distributed in a completely randomized design with 2x3x2 factorial arrangement (first beak trimming by means of infrared radiation or hot blade x the strains Lohmann LSL, Hy-line W-36, and Lohmann Brown x with or without beak trimming at the tenth week of age), totaling twelve treatments with six replicates. Beak trimming by infrared radiation, in the first week of life, provides the same production results and egg quality as the conventional method by hot blade. There were no deaths from cannibalism for birds of the three strains that were not subjected to the second beak trimming; however, a decrease of 8% viability was observed in birds at the 63th week of age.
Keywords: welfare; egg production; infrared radiation; beak treatment